Systematic Literature Review : The Importance of Interlanguage Pragmatic in Japanese Language Learning - Wina Widia Hastuti; Nuria Haristiani (Mezurashii: Journal of Japanese Studies, 2025)
This research uses the SLR or Systematic Literature Review method which focuses on findings that show the importance of interlanguage pragmatic and its learning in language learning, especially for Japanese language learning. There are 15 articles published in the period 2019 to 2024 that focus on three categories; the types of pragmatic errors that commonly occur, interlanguage pragmatic learning strategies, and their effects on language skills. The results obtained are the importance of understanding interlanguage pragmatic in relation to second language acquisition (L2), as a form of prevention and minimizing the occurrence of pragmatic errors and as a positive impact in the form of improving language skills in order to comply with the social and cultural norms of the language mastered. An understanding of interlanguage pragmatics is needed in Japanese language learning which is full of and closely related to the social and cultural norms of the community. This shows the integration of teaching interlanguage pragmatic thoroughly as a prevention of pragmatic errors and bridging the gap, both in research and understanding of interlanguage pragmatic. Keywords : acquisition, interlanguage pragmatic,language, learning